Development of Learning Media "Dice" And "Poetry Box" on Poetry Writing Materials for Tenth Grade Students of Senior High School - Ulya, Chafit; Widyawati, Angelita; Febriana, Noerzada; Prassetiyo, Rizal Dwi; Sari, Rizky Wulan; Tifani, Tika (Al Hikmah: Journal of Education, 2022)
This study aims to develop a dice and box-based learning media with an internet-based learning model that uses various web pages on the internet, the web pages used include canva, google form and id.pillapp.com. This media is used as Indonesian language learning in the basic competence of poetry text at the high school level. The development of this learning media uses the Research and Development (R&D) method. in the Research and Development (R&D) method there are three main stages that must be carried out. The three main stages are initial information data collection, product development, and product validation trials. This research was conducted by conducting interviews with Indonesian language teachers at MAN 2 Madiun through the media zoom meeting to find out what media was used before and what obstacles were faced by educators at the school. Students are faced with difficulties in being able to determine the theme and choose the right diction so that the poetry has a beautiful rhythm, so learning dice and poetry boxes can be used as a solution for teachers to be able to motivate students to explore ideas and maximum poetry results. Learning poetry dice and boxes can also improve the means used by teachers in conveying poetry text learning material effectively, efficiently, and interestingly.